-6(1+3k)=-36-3k

Simple and best practice solution for -6(1+3k)=-36-3k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(1+3k)=-36-3k equation:


Simplifying
-6(1 + 3k) = -36 + -3k
(1 * -6 + 3k * -6) = -36 + -3k
(-6 + -18k) = -36 + -3k

Solving
-6 + -18k = -36 + -3k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '3k' to each side of the equation.
-6 + -18k + 3k = -36 + -3k + 3k

Combine like terms: -18k + 3k = -15k
-6 + -15k = -36 + -3k + 3k

Combine like terms: -3k + 3k = 0
-6 + -15k = -36 + 0
-6 + -15k = -36

Add '6' to each side of the equation.
-6 + 6 + -15k = -36 + 6

Combine like terms: -6 + 6 = 0
0 + -15k = -36 + 6
-15k = -36 + 6

Combine like terms: -36 + 6 = -30
-15k = -30

Divide each side by '-15'.
k = 2

Simplifying
k = 2

See similar equations:

| 2x^2-30x+75=0 | | x+6+2x=-x-4-2 | | 10p+4=-3+7p+1p | | -6(2x-3)+15=36 | | 9a^2+42at+49t^2= | | 5t+4=5+4t | | -6(2x-3)+15=33 | | -3(p+3)=-2(-2p-3)-2p | | [2x-7]=3 | | -2y+5x=12 | | 28n^2-96=-184n | | 5x-3=12+11 | | 7.4-5.3-9.2p=-2.6 | | 23+2= | | P=23+0.575x | | 25a^2-90a+81= | | 24x-16= | | 10-2x+5x=13 | | 3+5x=7x-11 | | 12345+122334567= | | 3(x-7)=18 | | 1/4(1)-5=y | | P=(20+0.5x)+0.15(20+0.5x) | | 1/4(1)-5= | | 6x+3z-y= | | v^4-64= | | 3(2x-5)-4x=33 | | 4566q= | | 4x^2+21x+15=0 | | 3*6-4/2= | | -8+4y=6+3y-2 | | 5(6+5b)=-27+6b |

Equations solver categories